Influence of boron nitride inclusions and degradation in creep rupture strength on creep rupture ductility of Gr.122. (4th July 2021) - Abe, Fujio
ABSTRACT: The creep rupture ductility has been investigated for Gr.122 at 550 to 650 o C for up to 112, 247.8 h. The obtained results are compared with those for Gr.91 and Gr.92. The degradation in reduction of area (RA) in Gr.122 is similar to that in Gr.92 but more significant than that in Gr.91. The boron nitride inclusions are responsible for the degradation in RA in Gr.92 and Gr.122. The creep ductility parameter λ of Gr.122 decreases with increasing test duration to small values less than 5 at 20, 000 h to 30, 000 h and then increases steeply to about 20 at long times at 650 o C. The RA and total elongation of Gr.122 decrease with increasing test duration to small values but then turn to increase at 625 o C and 650 o C and long times.